Analysis of outcomes of endovascular embolisation: A cross-sectional two-center study on 46 visceral artery pseudoaneurysms - Omar, Mohammad Koriem Mahmoud (CVIR Endovasc, 2021)
PURPOSE: Visceral artery pseudoaneurysms (VAPAs) are uncommon in clinical practice but may have serious clinical outcomes up to death. Endovascular management is a safe effective alternative option to traditional surgical procedures. This study assesses the outcome of different embolic materials and techniques used in the endovascular management of VAPAs. MATERIALS AND METHODS: This is a two-center retrospective analysis of endovascular embolisation of 46 VAPAs, with a mean pseudoaneurysm size of 13 ± 11.35 mm, that were urgently managed between July 2018 and March 2020. Patients’ presentations were GIT hemorrhage, intrabdominal hemorrhage, hematuria, and abdominal pain in 34.78%, 30.43%, 23.91%, and 10.87% respectively. Management using coils only was done in 28/46 patients (60.87%), NBCA glue only in 16/46 patients (34.78%), combined coils and NBCA glue in 1/46 patient (2.17%), and Amplatzer plugs only in 1 patient (2.17%). The management techniques were sac packing in 9/46 patients (19.57%), inflow occlusion in 28/46 patients (60.87%) and trapping in 9/46 patients (19.57%). All patients were followed-up for 1 year after the procedure. RESULTS: The overall clinical success and periprocedural complication rates were 93.48%, and 15.22% respectively, and 30-day mortality was zero. Clinical success was 92.86% in the coil subgroup (n = 28), and 93.75% in the NBCA glue subgroup (n = 16). The technical success rate was 100%. Effectiveness of the procedures during the follow-up was 97.83%. Target lesion re-intervention rate was 2.17%. CONCLUSION: Transarterial embolisation can provide high technical and clinical success rates with low periprocedural complication and re-intervention rates, as well as satisfactory procedure effectiveness in the management of VAPAs.